Effects of Cornus Mas L. on Blood Glucose, Insulin and Histopathology of Pancreas in Alloxan-Induced Diabetic Rats - Fatemeh Shamsi; Sedigheh Asgari; Mahmoud Rafieian; Somayeh Kazemi; Azadeh Adelnia (مجله دانشکده پزشکی اصفهان, 2011)
Background: Diabetes is a chronic disease characterized by elevated blood glucose levels and disturbances in carbohydrate, fat and protein metabolism. Cornus mas (cornaceae) is one of the major medicinal plants in Asian countries that cotained high level of anthocyanins with potential to prevent hyperglycemia and obesity. In this study, we investigated antidiabetic effects of cornus mas in compared to glibenclamid as a standard drug on alloxan-induced diabetic rats. Methods: Thirty two male Wistar rats (190-240 g) were divided into four groups (n = 8): group 1 nondiabetic rats, group 2 alloxan-induced diabetic rats with no treatment, group 3 alloxan-induced diabetic rats treated with glibenclamid (0.6 mg/kg body weight) and group 4 alloxan-induced diabetic rats treated with cornus mas fruit 2 g daily for 4 weeks. Diabetes was induced by single intraperitoneal injection of alloxan 120 (mg/kg body weight). Findings: The results indicated that treatment with cornus mas fruit orally significantly reduced blood glucose levels and increased insulin levels in treatment of diabetic rats compared with no treatment diabetic group. Concurrent histological studies of the pancreas demonstrated the same results. On the base of histological results, cornus mas have a significant on increasing the size of pancreatic islets than diabetic groups (P < 0.05). Conclusion: Our results showed that cornus mas fruit has antidiabetic effects and can improve pancreas damage caused by free radicals in diabetes. The effects of this fruit can occur due to the presence of anthocyanin and other antioxidant compounds.